Detection and characterization of the cowpea chlorotic mottle virus in forage peanut (Arachis pintoi) in Brazil - Pantoja, Késsia Fátima Cunha [UNESP]; de Jesus Boari, Alessandra; De Marchi, Bruno Rossitto; Rezende, Jorge Alberto Marques; Kitajima, Elliot Watanabe; Gonçalves, Rivadalve Coelho; Assis, Giselle Mariano Lessa; Krause-Sakate, Renate [UNESP] (Springer Nature, 2024)
The cowpea chlorotic mottle virus (CCMV) was detected in forage peanut plants (Arachis pintoi), showing mosaic, yellowing, and interveinal chlorosis. Negatively stained partially purified preparations contained isometric particles ca. 30 nm in size, also present in the cytoplasm and vacuole of leaf parenchymal cells from CCMV-infected A. pintoi leaves. Mechanical transmission of the CCMV leaf extracts from symptomatic A. pintoi plants resulted in systemic mosaic in A. pintoi cv. BRS Mandobi, Vigna unguiculata L. cv Pretinha, and V. unguiculata sg. sesquipedalis cv. De Metro plants; mottle on leaves of inoculated Nicotiana occidentalis and N. benthamiana; and local necrotic and chlorotic lesions in Chenopodium quinoa and C. amaranticolor, respectively. High-throughput sequencing (HTS) allowed us to identify the causal agent as the CCMV and obtain the complete nucleotide sequence of the three genome components. BLAST search in the nucleotide database revealed high identities of the genome components with previously reported CCMV isolates. Primer was designed based on the HTS-derived sequence and efficiently detected CCMV in the infected A. pintoi samples. To our knowledge, this is the first report of CCMV infecting forage peanuts.
Keywords: Bromovirus; CCMV; High-throughput sequencing